The Effect of Antenatal Care (ANC) Examination on the Incidence of Stunting in Toddlers - Nurul Tasya Amalia D; Asrini Safitri; Rizki Amalia (Indonesian Journal of Global Health Research, 2025)
Stunting is a serious problem experienced by Indonesian children due to chronic malnutrition that affects their growth and development, making them too short for their age and requires immediate action. The stunting rate in Indonesia is still quite high at 21.6% based on the results of the Indonesian Nutrition Status Survey (SSGI) in 2022. According to the World Health Organization (WHO) in 2020 Indonesia has the second highest prevalence of stunting in Southeast Asia, reaching 31.8%. Antenatal Care (ANC) is a health service that is carried out or given to pregnant women starting from the beginning of pregnancy until the time of delivery. The purpose of this literature review is to determine the effect of Antenatal Care (ANC) examination on the incidence of stunting in toddlers. Method is using the literature review with the PRISMA Flow Chart principle. Scientific articles or journals were downloaded from PubMed, Garuda Portal, and Google Scholar with SINTA IV and V standards. The keywords in this article search are Antenatal Care and stunting. 143 articles were found in the search results. All articles were selected based on the inclusion criteria, resulting in 11 research articles to be reviewed. The results showed that there was an effect of Antenatal Care (ANC) checks on the incidence of stunting in toddlers. ANC visits are one of the family approaches in the stunting prevention program.